Academic Senate Minutes 2010-04-29 - Academic Senate:::::::::
Chair Report. Agenda Approved. Minutes deferred. Consent items: Revisions to the Biology Minor – approved. Move of Organizational Development MA to Hutchins – approved. Candidates for Graduation May 2010 – approved. President Report. Provost Report. Vice President for Administration and Finance Report. Vice President of SAEM Report. Associated Students Report. Special Report: Fiscal Report on Athletics. Resolution Applauding U. S. House of Representatives recognition of Norooz approved. Results of Diversity Recommendations Survey Report. Statewide Senators Report. Resolution to Hold a Referendum of No Confidence in the Financial Management of Sonoma State University and a Call for the Resignations of President Ruben Armiñana and CFO/VP Larry Furukawa-Schlereth tabled. Format of proposed online forum regarding tabled motion referred to Executive Committee.